FORMULASI DAN FORTIFIKASI IKAN CAKALANG (Katsuwonus sp.) PADA BUBUR INSTAN SEBAGAI PANGAN FUNGSIONAL TINGGI PROTEIN DAN KARBOHIDRAT DALAM PENANGGULANGAN KASUS GIZI BURUK DI INDONESIA - Yusida, Ayumi; Rahmawati, Rahmawati; Utami, Tri Nur; Fachrozan, Ryan (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Problems of malnutrition and malnutrition are found in Indonesia. Prevalence less severe in infants in Indonesia reached 17.9% in 2010 with 4.9% severe malnutrition and undernourishment by 13%. Malnutrition are found in areas such as eastern Indonesia Gorontalo, NTB, NTT and Papua. Total prevalence of malnutrition in the province of 33.6% or 463 370 infants. Combination rice and tuna can be used as a functional food. One of the proposed solution is to create an instant porridge based tuna to overcome the problem of poor nutrition. The advantages of instant porridge-based fish skipjack is easy to prepare, rich in protein, has a power longer lasting, and easier to distribute. The purpose of the study was to determine the nutrient content of tuna, rice, and instant porridge skipjack as a whole, determine the effect of processing on nutrient composition of tuna and rice, instant porridge determine formulations skipjack proper, and in an effort to diversify the fishery products increasing fish consumption Indonesian society. Â Keywords: Â carbohydrate,instant porridge, malnutrition, protein